2008
DOI: 10.1007/s10517-008-0222-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of in vivo biocompatibility and dynamics of replacement of rat shin defect with porous granulated bioceramic materials

Abstract: Biocompatibility of porous granulated bioceramic materials (hydroxyapatite, beta-tricalcium phosphate, hydroxyapatite-b-tricalcium phosphate complex (80:20 wt%), carbonate-containing hydroxyapatite, and silicon-containing hydroxyapatite) was shown in a subcutaneous test on BDF1 mice. Dynamic (up to 8 months) observation showed gradual replacement of the granular substance with de novo forming bone tissue with hemopoiesis foci on a model of fenestral defect in the shin bone in Wistar rats. By the rate of resorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…As defined by the principle of osteoconduction, the graft particles serve as scaffold for the new bone growth in close proximity to surface and engulfed in the pores of biomaterial particles 46 leading to de novo bone formation in the space between the particles or the space created after their slow degradation. 21,[47][48][49] The formation of new bone appears to follow a similar pattern in this study as shown for both groups by micro-CT and histomorphometry, but there is a remarkable upregulated expression of TRAP in the BCP group. Even though both Often characterized as intermediate to slow.…”
Section: Groupsupporting
confidence: 82%
“…As defined by the principle of osteoconduction, the graft particles serve as scaffold for the new bone growth in close proximity to surface and engulfed in the pores of biomaterial particles 46 leading to de novo bone formation in the space between the particles or the space created after their slow degradation. 21,[47][48][49] The formation of new bone appears to follow a similar pattern in this study as shown for both groups by micro-CT and histomorphometry, but there is a remarkable upregulated expression of TRAP in the BCP group. Even though both Often characterized as intermediate to slow.…”
Section: Groupsupporting
confidence: 82%
“…Reduction of the particle size [4], an increase in porosity [5] and introduction of ionic substitutions, such as magnesium [6], sodium [7], fluorine [8] and/or carbonate [9], so as to mimic the composition and microstructure of biological apatite, have presented approaches to resolving this issue, though with limited success. Namely, even the least sparingly soluble calcium-deficient apatites usually resorb slower than the new bone tissue formation rate [10], whereas HAP with high porosity is weak even to compression and not suitable for load-bearing applications [11]. An alternative approach has comprised admixing more resorbable calcium phosphates, typically tricalcium [12] or dicalcium [13] phosphates, or other calcium compounds, such as sulfates [14] or carbonates [15], to pure HAP.…”
Section: Introductionmentioning
confidence: 99%
“…HA is widely used due to its excellent biocompatibility and osteoconductivity in dentistry [12,13], but its biodegradability is poor, as such, the graft material remains in defects for a long period of time and ultimately blocks new bone formation [14,15]. The effort to improve the degradation rate of HA through granting porosity faces a limitation since it results in weaker compressive strength unsuitable for load-bearing application [16].…”
Section: Introductionmentioning
confidence: 99%